Equivalent Systemic Exposure to Fluticasone Propionate/Salmeterol Following Single Inhaled Doses from Advair Diskus and Wixela Inhub: Results of Three Pharmacokinetic Bioequivalence Studies - Haughie, Scott (J Aerosol Med Pulm Drug Deliv, 2020)
Background: Wixela(®) Inhub(®) was developed to deliver inhaled fluticasone propionate/salmeterol (FP/S) combination as a substitutable generic equivalent to Advair(®) Diskus(®). These studies aimed to confirm the pharmacokinetic bioequivalence (BE) of FP/S after single doses of Wixela Inhub (test [T]) and Advair Diskus (reference [R]). Methods: Three open-label, randomized, two-way crossover, single-dose studies in healthy subjects (N = 66 each) compared the systemic exposure of FP and salmeterol after inhalation from three dose strengths of FP/S (100/50, 250/50, or 500/50 μg) delivered from T and R. Primary BE endpoints were the area under the plasma concentration-time curve from time = 0 to the last measurable concentration (AUC((0-t))) and the maximum observed plasma concentration (C(max)) for both FP and S. The BE acceptance criteria specified that the 90% confidence intervals (CIs) of the geometric mean T/R ratios for AUC((0-t)) and C(max) can be contained within 0.80–1.25 for both FP and salmeterol. Results: Wixela Inhub met the acceptance criteria for BE for FP and salmeterol at each dose strength. Estimated AUC((0-t)) and C(max) geometric mean ratios (T/R [90% CI]) for FP were, respectively, 1.04 (1.00–1.08) and 0.92 (0.87–0.96) for 100/50 μg FP/S, 1.07 (1.02–1.13) and 1.01 (0.95–1.07) for 250/50 μg, and 0.97 (0.92, 1.00) and 0.90 (0.86–0.93) for 500/50 μg. Estimated AUC((0-t)) and C(max) ratios for salmeterol were, respectively, 1.08 (1.04–1.11) and 1.00 (0.94–1.04) for 100/50 μg FP/S, 1.03 (0.99–1.07) and 0.93 (0.87–1.00) for 250/50 μg, and 1.00 (0.96–1.04) and 0.86 (0.81–0.91) for 500/50 μg. FP/S at all doses via both T and R was comparably well tolerated. Conclusions: Wixela Inhub was bioequivalent to Advair Diskus at all three dose strengths for both FP and S, providing direct evidence of equivalent systemic safety and indirect evidence for equivalent pulmonary deposition.